A new dimerous flowered species of Paepalanthus (Eriocaulaceae) from the Chapada Diamantina (Bahia, Brazil). - Picanço, Wellerson; Tajima, Aline S [UNESP]; Coan, Alessandra I [UNESP]; Gonçalves-Esteves, Vania; Trovó, Marcelo (FapUNIFESP (SciELO), 2025)
In this manuscript we describe and illustrate a new species of Paepalanthus ser. Dimeri (Eriocaulaceae) endemic to the Chapada Diamantina, Brazil. The new species, Paepalanthus pyatan Picanço & Trovó, is distinguished from the other Paepalanthus by the following set of characters: robust habit, inflorescences arising at the top of lateral branches, capitula with ca. 2-3 cm in diameter, outer involucral bracts larger than the inner ones, and dimerous flowers. A detailed comparison with P. niger, the morphologically most similar species is provided. The new species is known from two unprotected and closely located subpopulations, and should be considered as endangered (EN). We also provide comments on the species anatomy, ecology and distribution, as well as distribution map, field photographs and detailed line drawings.